Comparative, reusability and regeneration study of potassium oxide-based catalyst in deoxygenation reaction of WCO. (January 2022) - Hafriz, R.S.R.M.; Nor Shafizah, I.; Arifin, N.A.; Maisarah, A.H.; Salmiaton, A.; Shamsuddin, A.H.
Abstract: In this work, the comparative study on the performance of K2 O/SiO2 and calcined dolomite catalysts was conducted via deoxygenation of waste cooking oil (WCO). KSi catalyst has the potential as a deoxygenation catalyst due to mesoporous structure catalyst with high base properties which enhance oxygen removal. The result found that K2 O/SiO2 catalyst could be used in the deoxygenation of WCO generating a high yield of pyrolysis oil as compared to thermal deoxygenation and calcined dolomite catalyst. Besides that, the reusability and regeneration of the K2 O/SiO2 catalyst were evaluated in the deoxygenation reaction using WCO as a feedstock. Five consecutive runs of reusability test and three successive cycles with two regenerations were performed. The reusability and followed by regeneration tests were conducted at conditions: 30 min of reaction time, 390 ± 5 °C reaction temperature and 150 cm 3 /min of N2 flow rate. The liquid products obtained from each cycle were analyzed by GC–MS. The deoxygenation of WCO using K2 O/SiO2 catalyst rendered higher selectivity towards diesel products (C13 -C24 ). The K2 O/SiO2 catalyst presented a good performance in reusability and regenerability test with only ∼19.3–22.4% dropped in pyrolysis oil yield after 5 consecutive runs and only ∼11.20–13.23% drop in diesel yield after regeneration. The results showed that K2 O/SiO2 catalyst has tremendous stability in the deoxygenation of WCO into green diesel and could be the alternative deoxygenation base catalyst for the deoxygenation process.